The Effectiveness of Cognitive Self-Compassion Training on Cognitive Emotion Regulation Strategies among Female Student with Generalized Anxiety Disorder - حسنعلی ویسکرمی; فاطمه رضایی; لیلا منصوری (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2017)
Aim and Background: Generalized anxiety disorder (GAD) is the most common type of anxiety disorder and has high rates of comorbidity with other psychiatric disorders. Sever anxiety is the main diagnostic criteria for GAD. The purpose of this study was to investigate the effectiveness of cognitive self-compassion training on cognitive emotion regulation strategies in female second grade high school students with GAD. Methods and Materials: The present experimental study was conducted with pretest-posttest design and a control group. The statistical population of this study consisted of all female second grade students of high schools in Izeh, Iran, in the academic year of 2015-2016. Screening was conducted and 302 participants completed the Penn State Worry Questionnaires (PSWQ), then, 40 individuals with GAD were identified and randomly assigned to experimental and control groups. The instrument used in this study was the Cognitive Emotion Regulation Questionnaire (CERQ). The experimental group received 10 sessions of self-compassion training lasting 90 minutes, 1 session per week, for 2 months. Data analysis was performed using descriptive and inferential tests such as ANCOVA. Findings: The results showed that self-compassion training significantly decreased self-blame, rumination, and catastrophising, from among maladaptive emotion regulation strategies, in the experimental group. From among adaptive emotion regulation strategies, it only effected positive reappraisal in the experimental group. Conclusions: Based on the results, it can be concluded that cognitive self-compassion training is an important factor in reducing some maladaptive cognitive emotion regulation strategies in students with GAD.